Clinical Study of DLBS2411, a Mucoprotector and Proton Pump Inhibitor Bioactive Fraction Derived From Cinnamomum burmanii, on the Intragastric Acidity - Tjandrawinata, Raymond Rubianto; Abdullah, Murdani; Simadibrata, Marcellus; Susanto, Liana W; Renaldi, Kaka (The Indonesian Society for Digestive Endoscopy, 2025)
Background: DLBS2411, A bioactive fraction derived from the bark of Cinnamomum burmanii has been developed to address acid-related gastrointestinal disorders. This study evaluated the pharmacodynamic effect of DLBS2411 on the 24-hour intragastric acidity in healthy adults. Methods: In a 3-arm, parallel, double-blind, randomized, placebo-controlled clinical trial, healthy subjects received a single dose of DLBS2411 (250 mg or 500 mg) or placebo. Gastric pH was monitored, analyzed and profiled over 24 hours. Results: Of a total of 54 enrolled male subjects, 47 subjects (87.04%) were eligible for the analysis. The mean 24-hour intragastric pH for DLBS2411 250 mg and 500 mg was 2.29 ± 0.42 and 2.13 ± 0.50, respectively, both higher than placebo (1.93 ± 0.70). Differences were more pronounced during the first 12 hours (daytime). DLBS2411 250 mg and 500 mg reached a gastric pH 4 significantly faster (129.9 ± 128.2 and 92.9 ± 106.8 minutes) compared to placebo (196.9 ± 99.7 minutes). No serious adverse events occurred. All adverse events were mild and had been resolved by the end of study, confirming the safety and tolerability of DLBS2411 at the dose of 250 and 500 mg. Conclusion: DLBS2411 effectively suppressed the intragastric acidity and demonstrated a good safety profile in healthy adults. These findings warrant further studies of DLBS2411 in patients with gastric acid-related disorders. Keywords: Alternative medicine, DLBS2411 cinnamomum burmanii, healthy volunteers, intragastric-acidity, proton pump inhibitors